Մի եզակի մագաղաթյա տպագրություն (Մաշտոցյան Մատենադարանի ձեռ. Հմր 10665) - Ղազարյան, Դավիթ (Մատենադարան)
The collection of Matenadaran comprises not only manuscripts but also oldprinted books, among which there is a notable Gospel, wholly printed except for its miniatures and a later colophon. When entering Matenadaran in 1974, it was placed in the manuscript depository and numbered № 10665. The Gospel is also unique for being printed on parchment. It has attracted specialists’ attention but they have not succeeded in finding out its date and the name of the printing-house. We have been able to find the answers to these questions: the Gospel was printed in the printing-house of Barsegh and Hakob Sebastatsʻi (in Constantinople) in 1740. Also, a more detailed study made it possible to identify the authors of illustrations: they are the same brothers Barsegh and Hakob who were famous painters in Constantinople. Among the manuscripts of Matenadaran, there is a Miscellany (M 101) which, according to the colophon, was illuminated by them. В коллекции Матенадарана наряду с рукописями хранятся также старопечатанные книги, среди которых особняком стоит одно Евангелие, полностью печатное, за исключением миниатюр и одного колофона. В 1974 году, при поступлении в Матенадаран, оно попало в рукописный фонд (№ 10665). Евангелие уникально еще и тем, что полностью напечатано на пергаменте. После поступления оно привлекло внимание ряда специалистов, которые так и не смогли выяснить дату издания и типографию. Нам удалось найти ответы на эти вопросы: Евангелие напечатано в типографии Барсега и Акопа Себастаци (Константинополь) в 1740 году. При более детальном изучении удалось также выяснить, что авторы иллюстраций – те же братья Барсег и Акоп, известные в Константинополе миниатюристы. Среди рукописей Матенадарана есть Сборник (№ 101), который, судя по колофону, иллюминировали те же братья.
Keywords: Արվեստ